The Color of paradise - Majidi, Majid, 1959-; Ramaz\0324ani, Muhsin; Mahjub, Hossein; Feiza, Salime (Varahonar Film Co.] ; Distributed by Columbia TriStar Home Entertainment, 1999)
Mohammad joyfully returns to his tiny village on summer vacation from the Institute for the Blind in Tehran, unaware of his father's intention to disown him. Engaged to be married, the widowed man has kept Mohammad a secret from his fiancě, certain the boy's disability will destroy his only chance for happiness. With the wedding swiftly approaching Mohammad's future hangs precariously in the balance as his father struggles against his destiny, unable to see the wonder of life and love that is so clear to his son.